Donor fatigue phenomenon: Trend and circumvention in Northern Ghana - Awadari, Adam Cassia (Goodwood Publishing, 2020)
Purpose: This study examines the phenomenon of donor fatigue and its implication on donor funding for local-NGOs. It further explores alternative ways of generating funds locally. Research Methodology: Convenient sampling method was used for selecting the sample for the study. The design involves collecting data from five (5) selected international donors, thirty (30) partner organization staffs, twenty-two (22) direct beneficiaries and fifteen (15) team leaders/council members of the partner organizations. Results: Donor funds have been on the decline due to donor fatigue, over dependency syndrome, poor proposal writing, improper management of donor funds, frequent changes in the interest areas of donors, changes in the policy direction of donor countries and the increasing number of local-NGOs competing for the same funds. Limitation: The conclusion drawn may not be representative of all the NGOs in Ghana as they may not all have similar funding sources and challenges Contribution: The finding will serve as a guide and logical framework for existing and potential local-NGOs on donor requirements for funding. Keywords: Donor fatigue, Donors, Funding, Prospects, Local-NGOs, Dependency syndrome